Seeking the Pure Land in Tangut Art - Wang, Michelle C. (Dynamics in the history of religions, 2022)
An intriguing group of paintings in the collection of the Hermitage, originally from Karakhoto, features Amitābha Buddha receiving the soul of a devotee into the Western Pure Land. Due to the broad geographic distribution of welcoming descent imagery across medieval China, Korea, and Japan, the origins of this iconography have been keenly debated by scholars. This paper focuses on the motif of Amitābha’s welcoming descent in order to illuminate the stakes of transcultural research. Previous scholarship emphasised chronology, artistic style, and iconography in order to situate the paintings from the Tangut Empire (ca. 1038-1227, in Chinese sources known as Xixia 西夏) in between Song China (960-1279, 宋) and its neighbours. In contrast, I consider the mediating role played by print culture, as well as the material features of Tangut welcoming descent paintings that distinguished them from similar paintings produced elsewhere in Asia. In the process, I consider the transcultural resonances of this visual motif.